Ultrasonographic study of comparison of prostate volume and post void residual urine with age in north Indian population - Munsif, Tahsin; Haider, Syed Shabeeh; Tewari, Vineeta; Fatima, Mariyam; Sharma, Pradeep Kumar (Asian Journal of Medical Sciences, 2021)
Background: As men’s life expectancy increases, benign prostatic hyperplasia (BPH) is the significant cause of morbidity. BPH generally involves the central region of the prostate which gradually enlarges. Due to the central hypertrophic change of prostate the urethra is compressed and urinary outflow obstruction develops. Predictive risk factors associated with chance of developing urinary retention includes age, symptoms, urinary flow rate and prostate size. Estimation of accurate intravesical, residual urine has significant importance and serves as an index of adequacy of bladder emptying. Aims and Objectives: The study aimed to measure the post void residual urine volume with age in Prostate outflow obstruction and compare the prostate volume and post void residual urine with age by ultrasonography. Materials and Methods: The present study was performed in 100 patients. Transrectal ultrasonography was performed using 7.5 MHZ transrectal probe. Prostate volume was calculated with the help of inbuilt software, by measuring 3 dimensions of prostate in transverse and longitudinal sections. Transabdominal suprapubic ultrasound was done to measure post void residual urine. Results: It was seen that in the lower age groups, the prostate size was smaller, while in the higher age group it was higher (p>0.001). Minimum post void residual urine was seen in age group of 40-49 years (3.42 -+2.23ml). while maximum mean value was seen in the 70-79 years of age. Statistically a significant difference in mean was seen among different age groups (p<0.001). Conclusion: There is a significant correlation between age and post void residual urine volume and prostatic volume. The present study showed that PVRUV is a novel accurate non-invasive test for predicting prostate biopsy outcome that can easily be used by clinicians, alone or in combination with Prostate Volume in the decision-making for treatment.